Chinese herbal medicine is associated with higher body weight reduction than liraglutide among the obese population: A real-world comparative cohort study - Liao, Yu-Ning; Chen, Hsing-Yu; Yang, Ching-Wei; Lee, Pai-Wei; Hsu, Chiu-Yi; Huang, Yu-Tung; Yang, Tsung-Hsien (Frontiers in Pharmacology, 2022)
Introduction: In Taiwan, many people receive Chinese herbal medicine (CHM) as an alternative choice to help control body weight. However, the clinical effectiveness of CHM on weight control has not been well studied, while potential risks and adverse effects are still unknown. The aim of our study is to find out a safe and efficient treatment model of CHM for weight control compared to liraglutide in a real-world setting. Methods: we retrospectively analyzed obese subjects [body mass index (BMI)≧25kg/m2] from Chang Gung Research Database (2013-2018). We evaluated the effect on body weight and BMI changes in obese groups receiving CHM or western medicine (WM, represented liraglutide) within 180 days. The proportion of subjects who achieved 5% and 10% weight reduction was calculated as well. Furthermore, the potential adverse events were analyzed during the study period. Overlap weighting was used to balance the baseline differences between CHM and WM groups. Results: The full cohort comprised 1360 participants: 701 in the CHM group and 659 in the WM group. At baseline, the CHM group was younger (42.75±12.12 years old in CHM versus 52.31±11.7 years old in WM, p-value <0.001) and has more female subjects (77.6% in CHM versus 53.0% in WM, p-value <0.001). On the other hand, CHM users had lower body weight (79.83±15.66 kg versus 84.68±17.14 kg, p-value <0.001) and BMI (30.58±5.20 versus 32.84±6.95, p-value <0.001). At day 180, CHM users lost more body weight (-4.5±4.07 kg versus -2.15±4.05 kg, p-value <0.001) and higher reduction in BMI (-1.77±1.73 versus -0.9±2.14, p-value <0.001). A total of 53.21% (n=373) CHM users lost at least 5% of body weight (22.46% for WM users, p-value <0.001), and 18.97% (n=132) lost at least 10% of body weight (4.55% for WM users, p-value <0.001). The benefit remained consistent with and without overlap weighting. For adverse events, 18 cases of hypertension occurred in 659 subjects in the WM group (2.7%) in comparison to 1 of 701 subjects in the CHM group (0.1%). Conclusion: CHM led to clinically meaningful weight loss without serious adverse events in a real-world setting. Further clinical trials are warranted to validate this result.